Population variation in the trophic niche of the Trinidadian guppy from different predation regimes - Eugenia Zandonà (Nature Portfolio, 2017)
Abstract Population variation in trophic niche is widespread among organisms and is of increasing interest given its role in both speciation and adaptation to changing environments. Trinidadian guppies (Poecilia reticulata) inhabiting stream reaches with different predation regimes have rapidly evolved divergent life history traits. Here, we investigated the effects of both predation and resource availability on guppy trophic niches by evaluating their gut contents, resource standing stocks, and δ15N and δ13C stable isotopes across five streams during the wet season. We found that guppies from low predation (LP) sites had a consistently higher trophic position and proportion of invertebrates in their guts and assimilate less epilithon than guppies from high predation (HP) sites. Higher trophic position was also associated with lower benthic invertebrate availability. Our results suggest that LP guppies could be more efficient invertebrate consumers, possibly as an evolutionary response to greater intraspecific competition for higher quality food. This may be intensified by seasonality, as wet season conditions can alter resource availability, feeding rates, and the intensity of intraspecific competition. Understanding how guppy diets vary among communities is critical to elucidating the role of niche shifts in mediating the link between environmental change and the evolution of life histories.